SHARING SESSION WITH SCHOLARSHIP AWARDEE UNTUK MEMPERSIAPKAN MAHASISWA MELANJUTKAN STUDI - Fitri Aida Sari (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Education needs to be owned by every citizen to bring change for himself, society, country, and the world. To ensure that every citizen gets a proper and appropriate education, the state guarantees its citizens to get an education. This is stated in Pasal 31 Undang – Undang Dasar 1945. The implementation is reflected in free education starting from the Elementary School to the High School and Vocational High School. It does not stop there, even now the state provides various scholarships to facilitate citizens to obtain higher education. One of the scholarships offered is LPDP scholarship. LPDP is an Education Fund Management Institution that provides scholarships for the general public who wish to continue their studies at the tertiary level. Cirebon University, especially in the mathematics education study program, wants to prepare their students to achieve higher education. Therefore, the head of mathematics program, lecturers, and student association held a sharing session with the theme of getting your scholarship, continue your studies, and make your dreams come true. The purpose of this activity is to provide experience and motivation for students to continue their studies. The method in this activity is in the form of discussions with awardee of LPDP schoolarship both master and doctoral levels. The results of this activities showed that students had great enthusiasm to continue their studies and increased enthusiasm for obtaining scholarships both at domestic dan overseas.